COMBUSTION AND LEACHING BEHAVIOR OF TRACE ELEMENTS IN LIGNITE AND COMBUSTION BY-PRODUCTS FROM THE MUĞLA BASIN, SW TURKEY - Fotopoulou, M.; Siavalas, G.; İnaner, H.; Katsanou, K.; Lambrakis, N.; Christanis, K. (Bulletin of the Geological Society of Greece, 2010)
The Muğla Basin is one of the most well-documented coal basins of Anatolia, SW Turkey. Previous studies mainly focused on coal geology, as well as on the environmental impacts from trace elements emitted into the atmosphere during coal combustion. However, the environmental impacts from coal utilization also include groundwater contamination from hazardous trace elements leached from exposed lignite stockpiles or ash disposal dumps. In the present study a comparative assessment of the combustion, as well as the leaching behaviour of trace elements from sixteen lignite, fly ash and bottom ash samples under various pH conditions is attempted. The samples were picked up from three regions in the Muğla Basin, namely, these of Yeniköy, Kemerköy and Yatağan. Proximate and ultimate analyses were performed on all samples. Quantitative mineralogical analysis was carried out using a Rietveld-based full pattern fitting technique. The elements Ag, As, B, Ba, Be, Co, Cr, Cu, Fe, Ga, Hf, Li, Mn, Mo, Ni, Pb, Sr, U, V and Zn were grouped according to their volatility during combustion and their leachability in the various types of samples. The pH of the leaching agent little affected the leaching trends of most elements and the mode of occurrence proved to be the major factor controlling primarily combustion and to a lesser extent leaching. The elements were classified into 7 classes with increasing environmental significance with Mo, Sr and V being the most potentially hazardous trace elements in the Muğla region.